Rural Transition in Azerbaijan - Lerman, Zvi; Sedik, David (Lexington Books, 2010)
In 1995D96 the President of Azerbaijan, Heydar Alieyev, launched a program of agrarian reforms that caused a sweeping and irreversible shift from Soviet-style collective agriculture to individual farming in his country. These reforms led to an impressive recovery and substantial productivity improvements in agriculture. The agrarian transition in Azerbaijan contrasts with that in Russia, Ukraine, and Kazakhstan, where land privatization has been accompanied by policies encouraging the persistence of large corporate farms and where agricultural recovery has been much less impressive. For this reason Azerbaijan is today viewed as one of the few examples of successful land reform in the former Soviet Union. The impact of the Aliyev agrarian reforms went far beyond the recovery of agricultural production. The new policies had a significant impact on rural poverty and they were instrumental in increasing the incomes of Azerbaijan's large rural population, which relies on agriculture for a substantial part of the family budget. To understand the successes and limitations of land reform, Rural Transition in Azerbaijan evaluates the record of rural reforms, focusing on policy change, farm level performance, and the impact of reforms on rural incomes and rural family well-being-issues that today are at the core of the agenda in many international organizations.